Promoting Mentalizing in Pupils by Acting on Teachers: Preliminary Italian Evidence of the “Thought in Mind” Project - Valle, Annalisa; Massaro, Davide; Castelli, Ilaria; Sangiuliano Intra, Francesca; Lombardi, Elisabetta; Bracaglia, Edoardo; Marchetti, Antonella (Frontiers in Psychology, 2016)
Mentalization research focuses on different aspects of this topic, highlighting individual differences in mentalizing and proposing programs of intervention for children and adults to increase this ability. The “Thought in Mind Project” (TiM Project) provides training targeted to adults―teachers or parents―to increase their mentalization and, consequently, to obtain mentalization improvement in children. The present research aimed to explore for the first time ever the potential of training for teachers based on the TiM Project, regarding the enhancement of mentalizing of an adult who would have interacted as a teacher with children. For this reason, two teachers – similar for meta-cognitive and meta-emotional skills - and their classes (N=46) were randomly assigned to the training or control condition. In the first case, the teacher participated in training on the implementation of promotion of mentalizing in everyday school teaching strategies; in the second case the teacher participated in a control activity, similar to training for scheduling and methods, but without promoting the implementation of mentalization (in both conditions two meetings lasting about three hours at the beginning of the school year and two supervisions during the school year were conducted). The children were tested by tasks assessing several aspects of mentalization (2nd and 3rd order false belief understanding, Strange Stories, Reading the mind in the Eyes, Mentalizing Task) both before and after the teacher participate in the TiM or control training (i.e. at the beginning and at the end of the school year). The results showed that, although some measured components of mentalization progressed over time, only the TiM training group significantly improved in 3rd order false belief understanding and changed - in a greater way compared to the control group - in two of the three components of the Mentalizing Task. These evidences are promising about the idea that the creation of a mentalizing community promotes the mentalization abilities of its members.